Синтез і дослідження електрокінетичного потенціалу наночастинок металів, отриманих з використанням екстрактів лікарських рослин - Rieznichenko, L.S.; Podolska, V.I.; Yakubenko, L.M.; Gruzina, Т.G.; Grishchenko, N.I.; Voitenko, O.Yu.; Dybkova, S.M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2026)
Extracts of medicinal plants contain a set of specific compounds that can ensure the formation of metal nanoparticles and at the same time provide them with useful properties for effective use in various fields of biotechnology, in particular in agricultural production. The main goal of this work was to synthesize and study the electrokinetic potential and structural properties of green synthesis products - silver, gold, zinc oxide, and iron oxide nanoparticles, depending on the composition of the plant material used and the synthesis conditions. 18 samples of metal nanoparticles were synthesized using aqueous and alcoholic extracts of medicinal plants: eucalyptus (Eucalyptus viminalis Labill), aloe (Aloe arborescens Mill and Aloe vera L.), peppermint (Mentha?piperita L.), plantain (Plantago major L.), chamomile (Matricaria chamomilla L.), nettle (dioecious Urtica dioica L.), willow-herb (Chamerion angustifolium L.), calendula (Calendula officinalis), hibiscus (Hibiscus sabdariffa L.), and an aqueous tannin solution. All samples were characterized by the content of polyphenolic compounds. The nanoparticles were studied by microelectrophoresis, UV-visible spectroscopy, dynamic light scattering (DLS), scanning electron microscopy (SEM), and X-ray diffraction (XRD). According to the obtained values of the electrokinetic potential, the sample synthesized using an aqueous extract of willow-herb tea proved to be the most stable among the obtained ZnO nanoparticles. Among the FexOy NPs, the most stable were nanoparticles synthesized using aqueous extracts of hibiscus and plantain. The most stable Au nanoparticles were the samples synthesized using tannin and an alcoholic extract of Aloe vera L. As for silver nanoparticles, tannin, an alcoholic extract of eucalyptus, and an aqueous extract of Aloe arborescens contributed to the formation of the most stable nanoparticles. These samples of Ag, Au, FexOy, and ZnO nanoparticles are the most promising for their further practical application, in particular in agroecology and crop production to combat phytopathogens and ensure soil health.